Comparative chemical study and antimicrobial activity of essential oils of three Artemisia species from Egypt and Saudi Arabia. (18th August 2019) - Amin, Sahar M.; Hassan, Hossam M.; El Gendy, Abd El‐Nasser G.; El‐Beih, Ahmed A.; Mohamed, Tarik A.; Elshamy, Abdelsamed I.; Bader, Ammar; Shams, Khaled A.; Mohammed, Rabab; Hegazy, Mohamed‐Elamir F.
Abstract: The chemical composition of essential oils (EOs) distilled from three wild Artemisia species, Artemisia herba‐alba, Artemisia judaica, and Artemisia monosperma, collected from Egypt, and Saudi Arabia, were analysed by gas chromatography–mass spectrometry (GC‐MS). The antibacterial activities of the EOs for all species were determined using the Agar disc diffusion method. The yield of the EOs ranged from 0.16 to 0.49%. The results showed that A. monosperma plants growing in Saudi Arabia gave the highest yield, compared with A. herba‐alba, A. judaica, and A. monosperma collected from Egypt. In total, 92 volatile compounds were identified from the aerial parts of the plants using GC‐MS. Oxygenated monoterpenes were the major class in A. herba‐alba (75.31%) and A. judaica (83.07%), whereas monoterpene hydrocarbons were the major representative group in A. monosperma collected from both Saudi Arabia (34.23%) and Egypt (36.23%). Yomogi alcohol (22.4%), artemesia alcohol (9.91%), and 1, 8‐cineole (9.68%) were the major components of the EO of A. herba‐alba, whereas camphor (31.4%), piperitone (29.9%), and endo ‐borneol (5.72%) were characterized as the main compounds in A. judaica . β‐Vinylnaphthalene (24.89%), β‐eudesmol (15.41%), and β‐pinene (20.67%) represented the main components of the EO of Saudi Arabian A. monosperma, but β‐pinene (11.89%), (–)‐spathulenol (8.84%), p ‐cymene (8.83%), and shyobunone (7.05%) were the major components of the EO of Egyptian A. monosperma . Herein, a comparative analysis between the EOs of Egyptian Artemisia and those collected from Saudi Arabia was performed with principal components analysis (PCA) and agglomerative hierarchical clustering (AHC). The minimum inhibitory concentration (MIC) values ranged from 0.5 to2.5 μL per disc against different microorganisms. Artemisia judaica and A. monosperma (Saudi Arabia) plants had the highest MICs and A. monosperma (Egypt) had the lowest MIC, which may indicate different compositions as a result of climatic variation. Abstract : The chemical composition of essential oils (EOs) from three wild Artemisia species, A. herba‐alba, A. judaica, and A. monosperma, collected from Egypt, and Saudi Arabia, were analysed by principal components analysis (PCA) and agglomerative hierarchical clustering (AHC). The antimicrobial activity indicated that Artemisia judaica (Egypt) and A. monosperma (Saudi Arabia) plants had the highest MICs.